Antidepressants as Endocrine Disrupting Compounds in Fish - Thompson, William Andrew; Vijayan, Mathilakath M. (Frontiers in Endocrinology, 2022)
As antidepressant usage by the global population continues to increase, their persistent detection in aquatic habitats from municipal wastewater effluent release has led to concerns of possible impacts on non-target organisms, including fish. These pharmaceuticals have been marketed as mood-altering drugs, specifically targeting the monoaminergic signaling in the brain of humans. However, the monoaminergic systems are highly conserved and involved in the modulation of a multitude of endocrine functions in vertebrates. While most studies exploring the possible impact of antidepressants on fish have focused on behavioural perturbations, a smaller spotlight has been placed on the endocrine functions, especially those related to reproduction, growth, and the stress response. The purpose of this review is to highlight the possible role of antidepressants as endocrine disruptors in fish. While studies linking the effects of environmentally relevant levels of antidepressant on the endocrine system in fish are sparse, the emerging evidence suggests that early-life exposure to these compounds have the potential to alter the developmental programming of the endocrine system, which could persist as long-term and multigenerational effects in teleosts.